2011
DOI: 10.1111/j.1399-5618.2011.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of neuropsychological functioning in euthymic bipolar disorder: an update and investigation of moderator variables

Abstract: Current results suggest that generalized, rather than specific, cognitive impairment characterizes euthymic bipolar disorder. Age, illness duration, education, and clinical course may moderate these broad cognitive effects. Against this general impairment backdrop, there may be a relative preservation of crystallized verbal ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
202
4
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(247 citation statements)
references
References 24 publications
23
202
4
7
Order By: Relevance
“…In spite of this, there was individual variability where some patients displayed a greater neuropsychological decline, which was associated with a poorer psychosocial adaptation at the end of the follow-up. This finding endorses the fact that longitudinal studies are needed to shed more light on the relative progression of cognitive impairment in subjects with bipolar disorder (Mann-Wrobel et al 2011). The results of the follow-up studies provide clues about the disease process involved as they may contribute to the development of psychosocial and neuropsychological programmes for improving the currently low functional recovery rates in treated bipolar disorder patients (Gildengers et al 2009 ;Martínez-Arán et al 2011).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In spite of this, there was individual variability where some patients displayed a greater neuropsychological decline, which was associated with a poorer psychosocial adaptation at the end of the follow-up. This finding endorses the fact that longitudinal studies are needed to shed more light on the relative progression of cognitive impairment in subjects with bipolar disorder (Mann-Wrobel et al 2011). The results of the follow-up studies provide clues about the disease process involved as they may contribute to the development of psychosocial and neuropsychological programmes for improving the currently low functional recovery rates in treated bipolar disorder patients (Gildengers et al 2009 ;Martínez-Arán et al 2011).…”
Section: Discussionmentioning
confidence: 87%
“…Despite current evidence, the neuropsychological profile during euthymia has not yet been well established and substantial heterogeneity has been reported (Mann-Wrobel et al 2011). Emerging data suggest that patients with bipolar disorder exhibit cognitive impairment in attention, verbal memory and executive functioning during remission (Martínez-Arán et al 2004b ;Mur et al 2007 ;Torres et al 2007 ;Mann-Wrobel et al 2011). Several studies reveal that it is important to examine cognitive performance in euthymic bipolar disorder patients since there is a strong association between neuropsychological impairment and poor psychosocial functioning outcome (Wingo et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The size of the WSE treatment effect for digit span backward (0.51, medium effect) is comparable to that reported by Burdick and colleagues 13 in a subset of their euthymic bipolar subjects treated with a dopamine agonist, pramipexole. A recent meta-analysis 9 of cognitive impairments in euthymic bipolar disorder individuals indicated that working memory deficits were in the large (0.8) effect size range. Furthermore, in recently manic patients who were previously employed, Bearden and colleagues 12 showed that gains in working memory, episodic memory, and executive functioning robustly predicted (odds ratio > 10) occupational recovery by 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Medium to large effect size impairments have been reported in executive functioning, working memory, processing speed, episodic memory, fluency, and problem-solving and perceptual cognitive domains; in other words, a broad cognitive deficit although less severe than those reported in persons with schizophrenia. 9 In schizophrenia, cognitive impairments are consistently associated with poor functional outcomes. 10 Likewise, in 6 of 8 studies, cognitive impairments were linked to worse functioning in persons with bipolar disorder even after controlling for demographic, illness, and mood variables.…”
mentioning
confidence: 99%
“…Cognitive impairment is a well-established finding in both schizophrenia (eg ) and bipolar disorder (eg Mann-Wrobel et al, 2011. The pattern of impairment appears to be broadly similar in both disorders: poor performance is seen in most or all domains of neuropsychological function, but deficits are disproportionately marked in executive function, long-term memory and sustained attention.…”
Section: Schizoaffective Disorder: Neuropsychological Findings In Relmentioning
confidence: 99%